The Role of Yoga Education in the Dimension of Health Perspective - Srivastava, Dr Madhu (IJRDO- Journal of Educational Research, 2017)
The present study is an attempt to know the perception of students of secondary level about the role of Yoga education in the dimension of health in the schools of Delhi. Students of govt. schools have been selected randomly. The data were collected using questionnaire in the dimensions pertaining to the health such as physical fitness & relieve from countless ailments. After analysis of data, the results of the study is that all the practices of Yoga act through the existing mechanisms of health in human body and the beneficial changes that take place in the human system at all levels. Thus Yoga helps in the all round development of an individual, which is the main aim of education.